HUBUNGAN KUALITAS PELAYANAN KONTRASEPSI DENGAN TINGKAT KEPUASAN AKSEPTOR KB - Yulia Nur Isnaini; Reni Dwi Setyaningsih; Tophan Heri Wibowo (Viva Medika, 2014)
The quality of contraception services is called good, if the services are able togive satisfaction to acceptor and based on with ethics code and also fulfill withstandards of service. The facilities that available are not suitable with standards ofquality in providing services to acceptors, it can decrease the acceptor participants. The purpose of research is to know relationship between quality ofcontraception services and level of satisfaction acceptor in BPS Midwives of Sutiyah,Wiradadi Village, District Sokaraja, Purwokerto regency. This research used observation analytic method, with cross sectional approach.The population in this research was the acceptor family planning in BPS Midwives ofSutiyah. The sampling method was accidental sampling. Totaling subjects were 53respondents. Statistic analysis used in this research was statistic analysis spearmanrank. This research was done in BPS Midwives of Sutiyah, Wiradadi Village, DistrictSokaraja, Purwokerto regency at May 15th until Juny 14 th 2012.The results of the spearman rank correlation coefficient test was no relationship between quality of contraception services and level of satisfaction acceptor p-value =0.229 (Î± = 0,05 ). The Conclusion was not relationship between quality of contraception servicesand level of satisfaction acceptor. Key words : quality of contraception services, level of satisfaction acceptor